Optimization of the enzyme assisted extraction of essential oil from the leaves and branches of Cinnamomum cassia using Box-Wilson method - Bich, Hoang Thi; Huong, Le Mai; Chien, Nguyen Quyet; Thuy, Dinh Thi Thu; Thanh, Le Tat; Sy, Do Trung; Hang, Le Thi Thuy; Hai, Pham Hong (Vietnam Journal of Science and Technology, 2017)
The process of enzyme assisted extraction of essential oil from the leaves and branches of the Vietnamese aromatic plant Cinnamomum cassia was studied and optimized using a Box-Wilson central composite design consisting of 05 independent variables (pH, temperature T, time τ, concentration of the enzyme Laccase, and concentration of the enzyme Cellic Htec2) and two dependent variables (reducing sugar and yield of essential oil). Second-order polynomial equations were obtained for the responses, which fitted well with the experimental data. Optimal conditions for oil yield were found at pH = 5.2; T = 440C; τ = 5h30’; Laccase = 0.42 ml/g, and Cellic Htec2 = 1.15%. The experimental value (0.982% oil yield) was close to the predicted value (0.978%). The application of enzyme assisted extraction in combination with optimization using response surface methodology substantially improved the oil yield as compared with traditional method.